Prevalence and Molecular Characterization of Cysticercus tenuicollis Isolated from Some Intermediate Host in Kurdistan-Iraq - Ahmed Hama, Abdullah; Hama Zorab, Rostam; Mohammed Ali, Fatima; M. Salih, Awaz; Abdullah Hassan, Amer (Kurdistan Journal of Applied Research, 2018)
Cysticercus tenuicollis (C. tenuicollis) is the larval stage infection of Taenia hydatigena, a common tapeworm of dogs and other Canidae, which has a wide range of intermediate hosts including sheep, goat, cattle, deer, camel, horse, human and other wild ruminants, the disease spreads through a contaminated water, soil and food with feces of infected dogs or other carnivores, T. hydatigena lives in the intestinal of the definitive host (carnivores) and excretes a huge number of eggs with feces daily. The present study conducted to determine the prevalence rate and molecular characterization of C. tenuicollis among sheep and goats in Sulaimani province. A total of 14088 slaughtered animals were inspected postmortem from the new Sulaimani abattoir comprise, which involves 13395 sheep and 693 goats. The selected cysts were preserved in 70% Ethanol for DNA extraction and molecular study, The mt-CO1 gene was amplified with a conventional polymerase chain reaction (PCR), the PCR product purified and DNA sequencing for reverse and forward strands was determined by a genetic analyzer, the obtained sequences aligned with the DNA sequences of T. hydatigena in Iran, Turkey and Palestine, which deposited in GenBank under the following accession number (JQ710588), (JN827307) and ( KM032284) respectively. The prevalence rate of C. tenuicollis was 2.63% in sheep and 2.58% in goats. This result shows no significant differences of C. tenuicollis between sheep and goats (p>0.05). The nucleotide sequence alignment of cytochrome oxidase subunit 1 (CO 1) gene revealed that the amplified DNA fragment is belong to Taenia hydatigena and Echinococcus granulosus and the nucleotide sequences of T. hydatigena deposited in GenBank under accession number (MH638348). This finding concludes that the amplification of mt-CO1 gene cannot be depended on discriminate hydatid cyst and C. tenuicollis while the partial DNA sequences of mt-CO1 gene are significantly valuable to differentiate C. tenuicollis from hydatid cyst, which is completely different in the pathology and control.